Risk factors associated with low back pain in marines treated by the outpatient clinic of the Centro Medico Naval: Factores de riesgo asociados a la lumbalgia en marinos atendidos por consultorio externo del centro médico naval - Arellano-Hidalgo, Roxana (2019)
Objective: To determine the risk factors associated with low back pain in marines attended by an outpatient of the Centro Médico Naval in Lima in 2017. Methods: Cases and controls study that included 66 cases and 132 controls, obtaining the information from medical records of the personnel of the Peruvian Navy in activity attended by an outpatient of physical medicine and rehabilitation through a validated data collection form. For the calculation of the chi-square and the p-value; logistic regression was used to estimate the Odds Ratio (OR) and CI 95%. Results: Of the total population, the male sex was 90.4%, the median age was 26 years (IR: 36-77). The presence of low back pain was associated in the multivariate analysis with age (OR = 1.05; 95% CI (0.94 - 1.16)), service time (OR = 0.91; 95% CI (0, 81-1)), overweight or obesity (OR = 2.24; 95% CI (1.16-4.28)) and dyslipidemia, (OR = 2.00; 95% CI (1.47-5, 66)). Conclusion: The presence of low back pain in naval personnel associated with age, gender, nutritional status and dyslipidemia.